Cost-benefit Assessment of Congresses, Meetings or Symposia, and Selection Criteria to Determine if they are Predatory - Teixeira Da Silva, Jaime A.; Al-Khatib, Aceil; Sorooshian, Shahryar (Institute of Research and Development of Walailak University, 2017)
Not a single day goes by in which academics receive one or more emails inviting them to attend a congress, meeting or symposium (CMS). Increasingly, most of these invitations are for attending CMSs that lie beyond the scope of their fields of research, and are usually characterized by images of grandeur and finesse, enticing the invitee with claims of international status, the pompous nature of the steering committee, or the meeting’s sheer size and dimension, including a list of famed participants. In other cases, emphasis is placed instead on the exotic nature of the location, and the invitation often sounds more like a travel brochure than an invitation to join a professional CMS. In several cases, a promise to publish the CMS proceedings in an indexed database is made. It is difficult to judge the veracity and significance of such meetings at a distance, even more so through an email. However, when the balance sheet is drawn up, and the costs are assessed, including of travel, accommodation and meals, it is clear to see that most CMSs are simply traps to make money, and that true academic discovery is a secondary, or more distant, objective. This article draws readers’ attention to the need for making a cost-benefit analysis based on the criteria that we present before deciding on whether to attend a CMS, or not.